Upakara Bali Ethnomathematics Monopoly Media Based on Augmented Reality on Geometry Material - Pratiwi, Ni Luh Puspa; Suarjana, I Made; Werang, Basilius Redan (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the lack of integration of local wisdom and innovation of learning media in geometry material in grade II of Elementary School. This study aims to produce monopoly media of Balinese traditional ceremony ethnomathematics based on Augmented Reality in geometry material in grade II of Elementary School that is good for use in learning. This study adopts development research using the ADDIE model. Trial subjects included two material experts, two media experts, one grade II teacher, six grade II students for individual trials, and ten for small group trials. Data collection methods used were observation, interviews, document studies, and questionnaires. Data were analyzed using qualitative descriptive statistical analysis techniques and quantitative descriptive statistical analysis. The results of the study indicate that the monopoly media of Balinese traditional ceremony ethnomathematics based on Augmented Reality is valid and feasible to use. The assessment of material experts was 97.5% and media experts 99%, both of which were very well qualified. The response of the second grade elementary school teachers reached 100%, while the student response in the individual trial was 94.06% and the small group was 93.99%, all of which were very well qualified. It can be concluded that the innovation of Balinese ethnomathematics monopoly media based on Augmented Reality on geometry material in second grade elementary school is valid and feasible to be used in the learning process. This study has implications for the preservation of local wisdom through learning media in schools.